2010
DOI: 10.1007/s00040-010-0086-1
|View full text |Cite
|
Sign up to set email alerts
|

Biological notes on a fungus-growing ant, Trachymyrmex cf. zeteki (Hymenoptera, Formicidae, Attini) attacked by a diverse community of parasitoid wasps (Hymenoptera, Diapriidae)

Abstract: A number of wasps in the family Diapriidae, subfamily Diapriinae (Proctotrupoidea), are parasitoids that specialize on ant larvae. These wasps are abundant and diverse in the Neotropics, but little is known about their biology. We studied parasitism rates by an array of diapriine wasps that attack the larvae of fungus-growing ants, Trachymyrmex cf. zeteki, in a single population (near Gamboa, Panamá). Relatively little is known about the biology and natural history of these ants, so we also present data on col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Mycelial cover may act as a physical barrier against tiny parasitoid wasps. Observations that larvae of species from several attine genera with extensive mycelial covers are heavily parasitized by diapriinae wasps (Loiácono et al 2000;Fernández-Marín et al 2006a;Pérez-Ortega et al 2010) neither support nor refute this idea because we do not know if parasitism would be higher without the mycelial cover. These parasitoids are little studied, but they are relatively diverse and abundant in both Trachymyrmex and Cyphomyrmex, which have a low and high extent of fungal brood covering, respectively.…”
Section: Explanationsmentioning
confidence: 86%
See 1 more Smart Citation
“…Mycelial cover may act as a physical barrier against tiny parasitoid wasps. Observations that larvae of species from several attine genera with extensive mycelial covers are heavily parasitized by diapriinae wasps (Loiácono et al 2000;Fernández-Marín et al 2006a;Pérez-Ortega et al 2010) neither support nor refute this idea because we do not know if parasitism would be higher without the mycelial cover. These parasitoids are little studied, but they are relatively diverse and abundant in both Trachymyrmex and Cyphomyrmex, which have a low and high extent of fungal brood covering, respectively.…”
Section: Explanationsmentioning
confidence: 86%
“…Genera Eggs Larvae Pupae but the mycelial cover adheres directly to the cuticular surface instead of having an airspace in between, as is found between a pupa and its silk cocoon. The function of this behavior is not resolved, although three untested hypotheses have been proposed: (1) protection against predators such as army ants or parasitism by wasps (LaPolla et al 2002;Powell and Clark 2004;Fernández-Marín et al 2006a;Pérez-Ortega et al 2010); (2) protection against potentially adverse environmental factors (Mueller et al 2010); and (3) protection from microbial parasites (Lopes et al 2005;Mueller et al 2010). We focus our analyses on the third hypothesis, because there is ample evidence that the advent of attine fungus farming around 50 million years ago (Schultz and Brady 2008) has confronted these ants with multiple challenges from parasites that are absent in many other ants.…”
Section: Presence/absencementioning
confidence: 99%
“…Fernández-Marin et al [9] found that between 27% and 70% of the colonies of two species of Cyphomyrmex Mayr were parasitized by one species in Puerto Rico and by up to four concurrent morphospecies of diapriids in Panama. Similarly, Pérez-Ortega et al [7] reported that another fungus-growing ant, Trachymyrmex cf. zeteki, was attacked by a diverse community of diapriids in Panama, with a mean intensity of larval parasitism per ant colony of 33.9%, and prevalence across all ant populations of 27.2%.…”
Section: Psychementioning
confidence: 88%
“…As true for the most social insects, they accumulate significant stores of resources within their nests, attracting a diverse array of predators, microbial pathogens, and parasites [7]. We studied aspects of the intensity and prevalence of these littleknown diapriine wasps that attack the larvae of the fungusgrowing ant, Acromyrmex lobicornis Emery, and noted a remarkably diverse community of parasitoids within host population from four localities of La Pampa, Argentina [4,8].…”
Section: Psychementioning
confidence: 99%
See 1 more Smart Citation